Customer Satisfaction and Loyalty toward COWAY’s Product and Service Ecosystem in Malaysia - Oh Zi Jian; Nur Eidra Nabila binti Zukarnai; Nur Farah Husna binti Mohd Fauzi; Nur Fatin Hidayah binti Mohamad Fuzi; Nur Huwaidah binti Abdul Khalid; Keshav Maheshwari (International Journal of Tourism and Hospitality in Asia Pasific, 2026)
This study investigates the factors influencing customer satisfaction and loyalty toward the products and services offered by COWAY Malaysia within a rental-based home appliance model. Grounded in Expectation-Confirmation Theory, the study examines the effects of product quality, service quality, price and value perception, and customer support on customer satisfaction and loyalty. A quantitative survey was conducted among 122 current COWAY customers in Malaysia using a structured questionnaire, and the data were analysed using descriptive and regression analyses. The results indicate that service quality and price and value perception have significant positive effects on customer satisfaction and loyalty, while product quality does not show a significant influence. Customer support demonstrates a positive but weaker relationship with satisfaction outcomes. These findings suggest that customers perceive product quality as a baseline expectation, placing greater emphasis on service experience and perceived value. The study provides managerial insights for COWAY to strengthen service excellence, enhance value communication, and refine pricing strategies to sustain customer satisfaction and long-term loyalty in a competitive home appliance market.